Critical residues for structure and catalysis in short-chain dehydrogenases/reductases. - Filling, C; Berndt, K; Benach, J; Knapp, S; Prozorovski, T; Nordling, E; Ladenstein, R; Jörnvall, H; Oppermann, U (2002)
Short-chain dehydrogenases/reductases form a large, evolutionarily old family of NAD(P)(H)-dependent enzymes with over 60 genes found in the human genome. Despite low levels of sequence identity (often 10-30%), the three-dimensional structures display a highly similar alpha/beta folding pattern. We have analyzed the role of several conserved residues regarding folding, stability, steady-state kinetics, and coenzyme binding using bacterial 3beta/17beta-hydroxysteroid dehydrogenase and selected mutants. Structure determination of the wild-type enzyme at 1.2-A resolution by x-ray crystallography and docking analysis was used to interpret the biochemical data. Enzyme kinetic data from mutagenetic replacements emphasize the critical role of residues Thr-12, Asp-60, Asn-86, Asn-87, and Ala-88 in coenzyme binding and catalysis. The data also demonstrate essential interactions of Asn-111 with active site residues. A general role of its side chain interactions for maintenance of the active site configuration to build up a proton relay system is proposed. This extends the previously recognized catalytic triad of Ser-Tyr-Lys residues to form a tetrad of Asn-Ser-Tyr-Lys in the majority of characterized short-chain dehydrogenases/reductase enzymes.